The unique and common effects of emotional intelligence dimensions on job satisfaction and facets of job performance: an exploratory study in three countries. Issue 8 (17th March 2022) - Schlaegel, Christopher; Engle, Robert L.; Lang, Guido
Abstract: Previous empirical studies have either used a unidimensional or a multidimensional analytical approach to examine the consequences of emotional intelligence (EI). In this exploratory study we integrate and extend these two approaches, using a novel perspective to better understand the structure of the EI-job satisfaction and the EI-job performance relationship. Using commonality analysis and data from Germany, India, as well as the U.S. we partition the explained variance for job satisfaction, in- role performance, and extra-role performance into the variance that is uniquely explained by the individual EI dimensions and the variance that is common to sets of EI dimensions. We provide evidence that the EI dimensions are differently related to job satisfaction and job performance facets. Furthermore, the findings offer insights on how unique and common effects vary across countries. Partitioning the unique and commonly shared variance allows us to assess the true predictive power of individual EI dimensions and of sets of EI dimensions. Based on these findings, we discuss implications for theory development and provide future research directions.